The impact of magnetic field on pulsatile blood flow through multi-stenosed tube - Ghangas Jyoti; Sumeet Gill; Rajbala Rathee; Neha Phogat; Monika Srivastava; Tarun Yadav; Muhd Zu Azhan Bin Yahya; Serguei V. Savilov (Zaštita Materijala)
The flow of blood via a multi-stenosed blood vessel that is modeled as having two layers and passing through a porous media is altered by an external magnetic field, as stated in this paper. In our current research, the explicit solutions of pressure gradient and both central and peripheral velocities are evaluated using the Frobenius Technique. Pictorial representations of the pressure gradient data for various parameters are produced using MATLAB programming. The study proves that variations in the peripheral layer's thickness have an impact on the pressure gradient. These insights might help in the creation of more potent treatments for blood flow-related disorders.